Small bowel obstruction: a prognostic score index for surgery – a review - Danilo Coco; Silvana Leanza; Irene Fiume (Gastroenterology Review)
Bowel obstruction is an important cause of morbidity and mortality, accounting for nearly 30,000 deaths and more than $3 billion per year in direct medical costs. Small bowel obstruction (SBO) is caused mainly by postoperative adhesions. Adhesive small bowel obstruction (ASBO) is one of the leading causes of surgical emergencies and in particular of surgical emergencies that require an emergent operation. Hence, in this review article we attempted to narrate the role of the prognostic score index in the management of small bowel obstruction. Various prediction score index models developed by various authors were discussed in this review article, with the aim to delineate the role of the prognostic score index for making a decision about the surgery of patients suffering from SBO to prevent further complications like strangulation, malignancy etc. The use of prediction score index models was deliberated in this review article; widespread implementation in the treatment of patients with SBO has the potential to improve patient outcomes and reduce resource consumption.